Naija and the Construction of National Identity on a Virtual Community - Saheed Okesola (Journal of linguistics, culture and communication, 2026)
Both individually and collectively, people hold in high esteem things that make them unique at different points in intergroup interaction. People and groups pride themselves on the traits that set them apart from others (Harwood 2006). They hold the idea of identity negotiation and maintenance dear in their minds and continuously strive to make subtle statements about these various shades of identity. It is against the aforementioned that the present study examines how Naija is deployed in the construction of national identity and loyalty to a collective sense of belonging by Nigerians in online interaction. Drawing data from Nigeria’s leading online community (www.nairaland.com) and insights from Group Attachment Theory (GAT), the study demonstrates how Nigerians in online interaction construct national pride and identity, linguistic uniqueness, and loyalty to their country of birth through the use of Naija.